Microprobe-XRF Assessment of Nutrient Distribution in Soybean, Cowpea, and Kidney Bean Seeds: A Fabaceae Family Case Study - Montanha, Gabriel Sgarbiero; Romeu, Sara Luiza Zachi; Marques, João Paulo Rodrigues; Rohr, Lívia Araújo; De Almeida, Eduardo; Dos Reis, André Rodrigues [UNESP]; Linhares, Francisco Scaglia; Sabatini, Sabrina; De Carvalho, Hudson Wallace Pereira (American Chemical Society (ACS), 2022)
The present study explored microprobe X-ray fluorescence (XRF) spectroscopy for quantitative and space-resolved distribution of macro, i.e., potassium (K), phosphorus (P), sulfur (S), and calcium (Ca), and micronutrients, i.e., iron (Fe), zinc (Zn), and manganese (Mn) elemental composition in the cross-sectioned seeds of cowpea (Vigna unguiculata L.), kidney bean (Phaseolus vulgaris L.), and soybean (Glycine max L.) seeds, which are important agricultural species within the Fabaceae family. It unveils that both macro and micronutrients were heterogeneously distributed across seed tissues. Most of the P and S, Fe, Zn, and Mn were mainly found at the embryo axis tissues in all three Fabaceae species, whereas K was spread along the cotyledon and Ca was mostly observed trapped at the seed coat region. Furthermore, the Pearson correlation coefficient revealed a strong spatial correlation between P and S, and K and S in cowpea and soybean seed tissues, whereas Zn and Mn association was also recorded. Therefore, the μ-XRF technique is an important tool for assessing seed nutrient distribution, thus subsidizing the physiological role of nutrients in seeds and fostering innovative approaches for nutrient supply and biofortification. copy; 2022 American Chemical Society.
Keywords: cowpea; kidney bean; nutrients; seeds; soybean; μ-XRF